Higher-order knowledge and sensitivity. Issue 3 (25th April 2020) - Bjerring, Jens Christian; Gundersen, Lars Bo
Abstract: It has recently been argued that a sensitivity theory of knowledge cannot account for intuitively appealing instances of higher-order knowledge. In this paper, we argue that it can once careful attention is paid to the methods or processes by which we typically form higher-order beliefs. We base our argument on what we take to be a well-motivated and commonsensical view on how higher-order knowledge is typically acquired, and we show how higher-order knowledge is possible in a sensitivity theory once this view is adopted.